2007
DOI: 10.1590/s0100-879x2007000800007
|View full text |Cite
|
Sign up to set email alerts
|

Role of nuclear factor kappa B and reactive oxygen species in the tumor necrosis factor-a-induced epithelial-mesenchymal transition of MCF-7 cells

Abstract: The microenvironment of the tumor plays an important role in facilitating cancer progression and activating dormant cancer cells. Most tumors are infiltrated with inflammatory cells which secrete cytokines such as tumor necrosis factor-α (TNF-α). To evaluate the role of TNF-α in the development of cancer we studied its effects on cell migration with a migration assay. The migrating cell number in TNF-α-treated group is about 2-fold of that of the control group. Accordingly, the expression of E-cadherin was dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(61 citation statements)
references
References 22 publications
4
53
3
Order By: Relevance
“…17 TNF-a could directly stimulate TGF-b1 production, collagen deposition in the renal cortex, increased interstitial volume, and deteriorating renal fibrosis, 18,19 TNF-a might also play an important role in EMT, perhaps by modulating TGF-b1 activity. 20,21 In our study, continuous administration of metformin successfully reduced the expression of TNF-a and IL-6, but transient administration of metformin did not. Renal fibrosis was characterized by excessive accumulation of ECM proteins, including increased expression of a-SMA, Vimentin, and loss of E-cadherin.…”
Section: Discussioncontrasting
confidence: 47%
“…17 TNF-a could directly stimulate TGF-b1 production, collagen deposition in the renal cortex, increased interstitial volume, and deteriorating renal fibrosis, 18,19 TNF-a might also play an important role in EMT, perhaps by modulating TGF-b1 activity. 20,21 In our study, continuous administration of metformin successfully reduced the expression of TNF-a and IL-6, but transient administration of metformin did not. Renal fibrosis was characterized by excessive accumulation of ECM proteins, including increased expression of a-SMA, Vimentin, and loss of E-cadherin.…”
Section: Discussioncontrasting
confidence: 47%
“…Recent studies have suggested the role of ROS in the induction of EMT in cancer cells. ROS can activate Snail and lead to EMT (Cannito et al, 2008;Dong et al, 2007) (Fig. 1).…”
Section: Ros and Emtmentioning
confidence: 99%
“…Due to the activation of Nitric Oxide Synthase 2 (NOX2), CAMs can directly produce ROS resulting in CAFs recruitment and MMPs activation [43]. Moreover, by secreting the master pro-inflammatory cytokine TNF␣, CAMs prime the NF-kB activation in both stromal and cancer cells, which in turn up-regulates SNAI1 expression [44]. In response to intrinsic and extrinsic oxidative stress, CAFs support tumor growth and promote EMT changes in cancer cells by secreting growth factors and ECM degrading proteases.…”
Section: Status Redox and Hypoxia: Two Sides Of The Same Coinmentioning
confidence: 99%